Search for the standard model Higgs boson at the LEP2 Collider near √s = 183 GeV - BARATE, R. (Institutional Knowledge at Singapore Management University, 1999)
During 1997 the ALEPH experiment at LEP gathered 57pb−1 of data at centre-of-mass energies near 183 GeV. These data are used to look for possible signals from the production of the Standard Model Higgs boson in the reaction e+e−→HZ. No evidence of a signal is found in the data; seven events are selected, in agreement with the expectation of 7.2 events from background processes. This observation results in an improved lower limit on the mass of the Higgs boson: mH>87.9GeV/c2 at 95% confidence level.